Expression and purification of phage T7 ejection proteins for cryo-EM analysis - Nicholas A. Swanson (Elsevier, 2021)
Summary: Bacteriophages of the Podoviridae family densely package their genomes into precursor capsids alongside internal virion proteins called ejection proteins. In phage T7 these proteins (gp14, gp15, and gp16) are ejected into the host envelope forming a DNA-ejectosome for genome delivery. Here, we describe the purification and characterization of recombinant gp14, gp15, and gp16. This protocol was used for high-resolution cryo-EM structure analysis of the T7 periplasmic tunnel and can be adapted to study ejection proteins from other phages.For complete details on the use and execution of this protocol, please refer to Swanson et al. (2021).